KEBIJAKAN HUKUM PIDANA DI BIDANG HAK CIPTA - KUSUMO, BAMBANG ALI (Joglo, 2008)
ABSTRACTCriminalisation in Copyright Wet include actions which are done by people or Corporatie that do not have authorities to publishing right opzet or to reproduction right or to assighmentraight. For the entire of that actions will be given prison punishment and fine.Â Key word : Criminalisation, punishment